Comparative study of the effect of a new renewable paraffinic fuel on the combustion process of a light-duty diesel engine. (15th December 2019) - Soriano, J.A.; García-Contreras, R.; Gómez, A.; Mata, C.
Abstract: The effect of a new renewable paraffinic fuel on the combustion characteristics of a diesel engine was evaluated and compared to other fossil paraffinic fuel (GTL – Gas - To Liquid), to a Biodiesel (blend of soybean and palm oil) and a to a conventional fossil diesel (without Biodiesel). Five steady state modes were selected that cover the most part of the engine speed-torque map of the driving conditions established in the New European Driving Cycle (NEDC). At the lowest engine load modes (A and C), the start of heat release occurs after main injection but at the other three modes (E, G and I) thermal conditions favor combustion of the pre-injection, the start of combustion escalating with the cetane number of the fuels. Biodiesel shows the lowest combustion duration, being the behavior of Farnesane similar only at high engine load conditions. Although Farnesane and GTL are paraffinic fuels, the combustion duration with the biofuel is more than 5° shorter in modes G and I although its start of combustion takes place earlier. Highlights: Potential for the use of a new renewable paraffinic fuel, named Farnesane, on diesel engine was evaluated. Thermodynamic diagnosis of the combustion process was studied. Tests were carried out under different steady-state modes, some of them out of NEDC driving conditions. The effect of cetane number has more influence in delay ignition than chemical structure. At high engine load Farnesane shows lower combustion duration than GTL despite starting later.